Examining the ethnoreligious dimension of conflicts in Nigeria - Daniel Rimamtari Tuki (Humboldt-Universität zu Berlin, 2024)
Violent conflicts remain a nagging problem in Nigeria. Because Nigeria's population is polarized along ethnic and religious lines, conflicts that have nothing to do with ethnicity and religion often turn ethnoreligious owing to the ethnic and religious identities of the conflict actors. This often makes conflicts more violent and intractable. Although some studies have been conducted on the ethnoreligious dimension of violent conflicts in Nigeria, most of them are qualitative. There is generally a dearth of quantitative studies examining the ethnoreligious dimension of violent conflicts in Nigeria. In this dissertation, I use large-N survey data and econometric techniques to fill this gap. I focus specifically on two contemporary conflicts in Nigeria—i.e., the secessionist conflict in Nigeria's Eastern Region and the intercommunal violence between nomadic pastoralists and resident communities (especially those engaged in crop cultivation) over land and water resources. The three empirical chapters in this dissertation show that ethnicity and religion are crucial in understanding contemporary conflicts in Nigeria. While the topics of ethnicity and religion are contentious, their neglect in the analysis of violent conflicts prevents a holistic understanding of the problem. Solutions can sometimes be found in the places where we are least willing to look. – – Gewaltsame Konflikte sind nach wie vor ein drängendes Problem in Nigeria. Da die nigerianische Bevölkerung entlang ethnischer und religiöser Linien polarisiert ist, werden Konflikte, die nichts mit ethnischer Zugehörigkeit und Religion zu tun haben, aufgrund der ethnischen und religiösen Identitäten der Konfliktakteure oft ethnoreligiös. Dadurch werden die Konflikte oft gewalttätiger und unlösbarer. Obwohl einige Studien über die ethnisch-religiöse Dimension von Gewaltkonflikten in Nigeria durchgeführt wurden, sind die meisten von ihnen qualitativ. Generell mangelt es an quantitativen Studien, die die ethnoreligiöse Dimension von Gewaltkonflikten in Nigeria untersuchen. In dieser Dissertation verwende ich große N-Erhebungsdaten und ökonometrische Techniken, um diese Lücke zu schließen. Ich konzentriere mich speziell auf zwei aktuelle Konflikte in Nigeria, nämlich den Sezessionskonflikt in der Ostregion Nigerias und die Gewalt zwischen nomadischen Hirten und ansässigen Gemeinschaften (insbesondere denjenigen, die Ackerbau betreiben) um Land und Wasserressourcen. Die drei empirischen Kapitel dieser Dissertation zeigen, dass Ethnizität und Religion für das Verständnis der gegenwärtigen Konflikte in Nigeria von entscheidender Bedeutung sind. Die Themen Ethnizität und Religion sind zwar umstritten, aber ihre Vernachlässigung bei der Analyse von Gewaltkonflikten verhindert ein ganzheitliches Verständnis des Problems. Lösungen können manchmal dort gefunden werden, wo wir am wenigsten bereit sind zu suchen.
Keywords: 300; Conflict; Religion; Ethnicity; Nigeria; Konflikt; Religion; Ethnizität; Nigeria